Comparison of ciprofol and propofol for endoscopic retrograde cholangio-pancreatography anesthesia: a systematic review and meta-analysis - Wu, Kai; Liao, Min; Deng, Juan; Yu, Yunfeng; Yin, Yuman; Yang, Xinyu; Yu, Rong; Liu, Zhenjie (Frontiers in Pharmacology, 2025)
ObjectiveThe potential of ciprofol in endoscopic anesthesia is receiving increasing attention. Compared to propofol, ciprofol exhibits stronger sedative effects and requires a lower dosage. This study aimed to compare the safety of ciprofol and propofol in Chinese patients undergoing endoscopic retrograde cholangio-pancreatography (ERCP) anesthesia.MethodsA comprehensive literature search was conducted across eight common databases before 1 January 2025, including PubMed, Embase, the Cochrane Library, and Web of Science, China National Knowledge Infrastructure, China Science and Technology Journal Database, WanFang, and SinoMed. After screening the literature according to established standards, the meta-analysis and trial sequential analysis (TSA) were conducted using Review Manager 5.3 and TSA 0.9.5.10 beta, respectively. Finally, publication bias for each outcome was assessed using Harbord regression analysis.ResultsSeven randomized controlled trials (RCTs) with 1,264 participants undergoing ERCP were included, and all included studies were conducted in China, with participants representing the Chinese population. The meta-analysis showed that compared to propofol, ciprofol reduced bradycardia (risk ratio [RR] 0.44, 95% confidence interval [CI] 0.26–0.76, P = 0.003, n = 4), hypotension (RR 0.72, 95% CI 0.55–0.95, P = 0.02, n = 4), respiratory depression (RR 0.25, 95% CI 0.14–0.44, P < 0.00001, n = 5), hypoxemia (RR 0.35, 95% CI 0.21–0.58, P < 0.0001, n = 5), and injection pain (RR 0.17, 95% CI 0.11–0.26, P < 0.00001, n = 7), but had no significant effect on choking cough, involuntary movements, or nausea and vomiting. TSA showed a conclusive benefit for bradycardia, respiratory depression, hypoxemia, and injection pain, whereas the benefit for hypotension needs further validation. Harbord regression analysis showed no publication bias for any of the outcomes, except for hypotension.ConclusionCompared with propofol, ciprofol has been shown to reduce the incidence of bradycardia, respiratory depression, hypoxemia, and injection pain in patients undergoing ERCP; however, its effect on the occurrence of hypotension still requires further investigation. Future studies are warranted to clarify the safety, efficacy, and optimal dosing of ciprofol across various patient populations, particularly those with complex comorbidities. These efforts would facilitate the broader application of ciprofol in ERCP and other surgical procedures, such as gastrointestinal and ophthalmic surgeries.Systematic review registrationwww.crd.york.ac.uk/PROSPERO/view/CRD420251090047, identifer, CRD420251090047